2016
DOI: 10.1016/j.radonc.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for primary hepatic malignancies – Report of a phase I/II institutional study

Abstract: Background and Purpose-To report outcomes and toxicities of a single-institution Phase I/II study of stereotactic body radiotherapy (SBRT) in the treatment of unresectable hepatocellular cancer (HCC) and intrahepatic cholangiocarcinoma (IHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 25 publications
3
81
1
5
Order By: Relevance
“…Additional, smaller, prospective studies reported by Weiner et al 46 and Kim et al 48 demonstrated similar results (see Table 1). Collectively, these prospective studies (encompassing results from more than 350 patients with HCC) demonstrate that, for a well selected group of patients, HIGRT with photon-based therapy is an appropriate treatment option.…”
Section: Prospective Modern Trialssupporting
confidence: 70%
See 1 more Smart Citation
“…Additional, smaller, prospective studies reported by Weiner et al 46 and Kim et al 48 demonstrated similar results (see Table 1). Collectively, these prospective studies (encompassing results from more than 350 patients with HCC) demonstrate that, for a well selected group of patients, HIGRT with photon-based therapy is an appropriate treatment option.…”
Section: Prospective Modern Trialssupporting
confidence: 70%
“…Several prospective, nonrandomized studies have evaluated the use of HIGRT for treatment of HCC (Table 1). [43][44][45][46][47][48][49][50][51][52] These experiences suggest that HIGRT is well tolerated, with acceptable toxicities and excellent local control (LC) rates. However, follow-up is relatively short, and many trials have not reached a median survival endpoint.…”
Section: Prospective Modern Trialsmentioning
confidence: 99%
“…20 Recent studies have further characterized the dose volumetric parameters associated with increased toxicity. [29][30][31][32] We were not able to establish a dosimetric parameter to predict for toxicity, possibly due to the fact that grade 3 or higher events were very rare and the aforementioned study also included grade 2 or higher events. The only dosimetric finding in our study was that higher radiation doses were associated with a rise in CTP/ ALBI.…”
Section: Discussionmentioning
confidence: 98%
“…SBRT for hepatic malignancies has been evaluated in a phase I/II study including 26 patients which reported a median survival of 11.1 months, and 1-year OS rate of 45%, with adverse events including a decline in Child-Pugh score in 9 patients and 2 grade 5 hepatic failures [61]. A small study has also evaluated SBRT as a bridge to transplantation, concluding it is a feasible and well-tolerated bridging therapy which may prolong a patient's candidacy for a curative liver transplant [62].…”
Section: Role Of External Radiotherapymentioning
confidence: 99%